Reference Services and Public Policy, 1st edition - Irving, Richard D. (Routledge, 2020)
This book, first published in 1988, looks at the relationship between public policy and information and reports ways in which libraries respond to the need for public policy information. Chapters provide perspectives from a variety of library settings with different user groups who, in turn, have different information needs. This volume will stimulate you to examine the adequacy of your own reference services and to a greater appreciation of the dynamic relationship between public policy and information services.